Analisis Efisiensi Termal Kompor Biomassa Tipe Gasifier Downdraft dengan Variasi Massa Campuran Arang Kayu dan Wood Pellet - Joel Hasoloan Simatupang; Jufrizal Jufrizal; Supriatno Supriatno (CV. IRA PUBLISHING, 2025)
This study analyzes the thermal efficiency of a downdraft gasifier-type biomass stove using various fuel masses of wood charcoal and wood pellets. The Water Boiling Test (WBT) method was applied with fuel masses of 0.5 kg, 0.75 kg, 1 kg, and 1.5 kg. Observed parameters included thermal efficiency, fuel consumption rate (FCR), power input, and power output. The highest thermal efficiency, 14%, was achieved with 1.5 kg of wood pellets, while charcoal showed a decrease in efficiency at 1 kg. FCR increased with charcoal but decreased with wood pellets, indicating better combustion efficiency. Power input and output increased with higher fuel mass. These findings highlight the importance of fuel type and mass optimization in improving biomass stove performance, thereby supporting Indonesia's transition to renewable energy.